2011
DOI: 10.1590/s0102-36162011000600007
|View full text |Cite
|
Sign up to set email alerts
|

Características epidemiológicas e causas da fratura do terço proximal do fêmur em idosos

Abstract: Objective: The social and economic cost of proximal femoral fractures is high, due the morbidity and mortality relating to the fracture itself, among other factors. Despite the importance of this issue, studies on this topic are still scarce in Brazil. This was a retrospective, observational and cross-sectional (ecological) study with the aims of outlining an epidemiological profile for proximal femoral fractures among the elderly and analyzing the causes of these fractures and the physical characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
15

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
1
8
0
15
Order By: Relevance
“…Studies published previously also showed that women and individuals of advanced age presented fractures of the proximal femur more frequently, because of their association with osteoporosis. 1 , 18 , 23 , 24 , 25 The side predominantly affected by these fractures was the right side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies published previously also showed that women and individuals of advanced age presented fractures of the proximal femur more frequently, because of their association with osteoporosis. 1 , 18 , 23 , 24 , 25 The side predominantly affected by these fractures was the right side.…”
Section: Discussionmentioning
confidence: 99%
“…In the worldwide literature, we noted that, independent of the treatment method chosen, the time when the operation was performed or the previous level of autonomy, the patients’ degree of dependence increased considerably after surgical treatment. 23 , 30…”
Section: Discussionmentioning
confidence: 99%
“…6 A maior incidência de FQ em mulheres pode estar relacionada ao fato de o sexo feminino ter maior expectativa de vida e, portanto, estar mais exposto a fatores de risco, iniciar o processo de declínio de massa óssea antes do homem, ter maior suscetibilidade para quedas, além das influências antropométricas e dos fatores genéticos associados ao sexo. 7,13 Quando avaliada a média de idade, o resultado desta pesquisa foi de 79,4 anos (± 8,8), maior em comparação aos estudos feitos por Hungria Neto, Dias e Almeida, 14 com média de 75,8 anos, mas menor que o valor encontrado no banco de dados dos estudos epidemiológicos do Ministério da Saúde, 3 que fizeram referência à média de 83 anos. Todavia, os resultados aferidos estão em consenso com esta e outras análises, quando identificaram que há incidência maior de idosos com FQ na sétima e na oitava década de vida.…”
Section: Variáveis N Custo Total (R$) P** Mediana (P25 -P75)unclassified
“…15 Na classificação por tipos de fratura foram encontradas na amostra 83 (62%) fraturas transtrocantéricas e 51 (38%) fraturas de colo de fêmur, quantidades condizentes com a literatura. 1,6,8,14 A prevalência de comorbidades é alta entre os pacientes hospitalizados com FQ. 7 Idosos com fraturas por queda têm alta prevalência de comorbidades e elevado risco para complicações.…”
Section: Variáveis N Custo Total (R$) P** Mediana (P25 -P75)unclassified
“… 1 It occurs typically in individuals over the age of 60, especially in post-menopausal women, 2 usually due to low-energy trauma such as falls to the ground. 3 4 However, this type of fracture can also be observed in young patients and, in these cases, it relates to high-energy trauma such as automobile injuries. 5 6 …”
Section: Introductionmentioning
confidence: 99%